2010
DOI: 10.1186/1743-422x-7-114
|View full text |Cite
|
Sign up to set email alerts
|

A highly attenuated recombinant human respiratory syncytial virus lacking the G protein induces long-lasting protection in cotton rats

Abstract: BackgroundRespiratory syncytial virus (RSV) is a primary cause of serious lower respiratory tract illness for which there is still no safe and effective vaccine available. Using reverse genetics, recombinant (r)RSV and an rRSV lacking the G gene (ΔG) were constructed based on a clinical RSV isolate (strain 98-25147-X).ResultsGrowth of both recombinant viruses was equivalent to that of wild type virus in Vero cells, but was reduced in human epithelial cells like Hep-2. Replication in cotton rat lungs could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 28 publications
4
68
1
Order By: Relevance
“…Recent studies reported an important role for G protein and its receptor, CX3CR1, in the pathogenesis of RSV (14,32). In addition, it was shown that genetic ablation of the G protein reduces RSV infectivity in mice and cotton rats (7,8), indicating that viral entry of airway epithelial cells might be hampered without a functional G protein. The G protein expresses a CX3C motif which can bind to the CX3CR1 receptor and, hence, can facilitate viral entry in vivo in airway epithelial cells and in vitro in HAE cell cultures (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported an important role for G protein and its receptor, CX3CR1, in the pathogenesis of RSV (14,32). In addition, it was shown that genetic ablation of the G protein reduces RSV infectivity in mice and cotton rats (7,8), indicating that viral entry of airway epithelial cells might be hampered without a functional G protein. The G protein expresses a CX3C motif which can bind to the CX3CR1 receptor and, hence, can facilitate viral entry in vivo in airway epithelial cells and in vitro in HAE cell cultures (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is composed of the extracellular domain of the G protein and is shed within hours after infection in vitro (6). Although modified RSV strains lacking G protein are still infectious in vitro, infection in vivo is highly attenuated, underscoring the importance of the G protein (7,8). Successful infection in vivo thus seems to depend on the presence of a functional G protein.…”
mentioning
confidence: 99%
“…The propagation of virus and preparation of vaccine were described in detail previously (17). In brief, the HRSV that we used for infection and challenge experiments was wild-type HRSV-X (wtHRSV) (strain 98-25147-X).…”
Section: Methodsmentioning
confidence: 99%
“…HRSV is a good example, as infection, pathology, and protection induced by candidate HRSV vaccines in cotton rats have already been explored and reflect the human situation (11,12,(15)(16)(17). In comparison to young cotton rats, aged cotton rats express a prolonged cytokine response and a high degree of pathology in the lungs in response to a primary HRSV infection (18,19).…”
mentioning
confidence: 99%
“…Recombinant RSV virus lacking the G gene (⌬G-RSV) was generated by reverse genetics. The construction and characterization of this mutant have been described previously (43). The recombinant virus was cultured on monkey kidney Vero cells (ECACC lot 10-87/CCL-81; ATCC).…”
Section: Methodsmentioning
confidence: 99%